Conductive elastic sponge-based triboelectric nanogenerator (TENG) for effective random mechanical energy harvesting and ammonia sensing - Liu, Yupeng; Zheng, Youbin; Wu, Zishuai; Zhang, Liqiang; Sun, Weixiang; Li, Tinghua; Wang, Daoai; Zhou, Feng (Nano energy, 2021)
Triboelectric nanogenerator (TENG) based on elastic materials is increasing interests for irregular and random mechanical energies harvesting. However, the conductive design of the elastic materials in TENGs often limits its applications. Herein, a new conductive and elastic sponge-based triboelectric nanogenerator (ES-TENG) is developed for random mechanical energy harvesting, which integrates the elastic material and the conductive material on a flexible sponge to realize the collection of mechanical energies, particularly for irregular and random motions. The conductive elastic sponge is prepared by a simple dilute chemical polymerization of aniline to grow conductive polyaniline nanowires (PANI NWs) on the surface of elastic sponge. Due to the flexible deformation of sponge, it can harvest the kinetic energy of disordered motion with different amplitudes and from variable directions. As the triboelectric layer of ES-TENG, the porous sponge and polyaniline nanowires on its surface can provide a large contact area and improve the triboelectric efficiency. At the same time, the conductive polyaniline coating on the surface of sponge can also be used as the electrode of ES-TENG to conduct electrons and generate an output of 540 V and 6 μA respectively, which can be used on various flexible object surfaces to collect irregular and random mechanical energy ubiquitous in daily life. In addition, based on the NH3-sensing performance and the three-dimensional reticular structure of the polyaniline nanowires on the elastic sponge, the ES-TENG can make it work as self-powered sensor for detecting toxic NH3 with the detection limit up to 1 ppm and the response time less than 3 s. In view of the microporous and nanowire structures, elasticity, conductivity and easy fabrication of the conductive elastic sponge, the ES-TENG has promising applications in various irregular and random mechanical energy harvesting and self-powered NH3 sensors. [Display omitted] •A new conductive elastic sponge-based triboelectric nanogenerator (ES-TENG) is developed.•The conductive elastic sponge is prepared by a dilute chemical polymerization of aniline on the surface of sponge.•The ES-TENG can conveniently harvest irregular and random mechanical energies.•The ES-TENG based self-powered NH3 sensor has detection limit up to 1 ppm and fast response of less than 3 s.